Moelcular characterization of the promoter region of the nuclear factor Kappa-B Subunit 1 (NFKB1) gene; Towards its involvement in susceptibility to obesity in Malay obese attributes - Atif, Amin Baig; Ahmad Zubaidi, A.latif; Nordin, Simbak; Tengku Mohammad Ariff, Raja Hussin (2017)
The nuclear factor kappa-B subunit 1 (NFKB1) gene at 4q24 encodes a 105 kD protein which can undergo cotranslational processing by the 26S proteasome to produce a 50 kD protein. The 105 kD protein is a Rel protein-specific transcription inhibitor and the 50 kD protein is a DNA binding subunit of the NFKB protein complex. The NFKB protein is a pleiotropic transcription factor present in most of the cell types and is the endpoint of a series of signal transduction proceedings that are initiated by a vast array of stimuli related to many biological processes such as immunity, differentiation, cell growth, apoptosis, inflammation and tumorigenesis. It has been postulated to be the integrated molecule between obesity and hypoxia.This study aimed to perform molecular characterization of the human NFKB1 promoter region.The sequence of the promoter region of the human NFKB1 (Accession no. AY515254) was obtained from Gene bank. The open reading frames (ORFs), restrictions/methylation sites against a total of 560 recognition sequences, a total of three TATA boxes (TATA, tata, Goldberg Hogness Sequences) were identified using clustal X feature of VectorNTI. Transcriptional factors binding sites (TFBS) were identified using online tool. Promoter prediction was determined by doing manually matching of TFBS with TATA box from outward in. These manual findings were compared with online promoter prediction results. A total of 4 ORFs were identified, A total of two vital restrictions sites; AvaI (-177bp) and BamHI (-201 bp) were found. Four TATA boxes [TATA (TATAA): at - 219 bp (100.0% similar) on complementary strand, tata (TTGACA): at -281 bp (83.3% similar) on complementary strand and -271 bp (83.3% similar) on complementary strand, and Goldberg–Hogness (TATAAAA): at -221 (100.0% similar) on complementary strand] were identified. Thirty five TFBS were found online, five TFBS (GR-beta, TFIID, TBP, MEF-2A, and HNF-3alpha) matches exactly with TATA box (TATAA), position -219 bp. In the online promoter prediction, prediction transcription start site (TSS) was not found. Till date this is the first study characterizing the molecular motifs and crucial elements within the reported promoter region of NFKB1 though successfully characterized in this study, there is a serious need to study the involvement of these motif in the transcriptional regulation of NFKB1 in future studies as per the role of these transcriptional factors in cell proliferation and motility in obesity and hypoxia.